Penanaman Nilai-Nilai Moderasi Islam Bagi Siswa di Sekolah Umum - Rusmayani Rusmayani (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
Public school in Bali is a school consisting of various tribes, races, religions, and cultures. With heterogeneous public conditions, public schools are susceptible to disputes, so it is absolutely necessary to plant the values of moderation of islam by PAI teacher, through a process of teaching in the classroom and through the attitude shown in the life everyday life at school. This provision as not only prepare students of the hereafter but rather Scrip in the living world, given the number of Muslim students who pretty much was educated in public schools. SD 3 Sesetan, SD N1 Abianbase, Bali Kiddy School, and SD Star Persada is one public school in Bali. The school is led by principal hindu. Understanding the values of moderation of islam as a concept of a moderate religious understanding, into the basic capital as the biggest minority Muslims in Bali in living a life of community